PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE BINGO REVIEW TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN BARIANG RAO-RAO KABUPATEN SOLOK SELATAN - Oktafia, Riri; Haryono, Yulia; Mardiyah, Ainil (Pendidikan Matematika, 2014)
Â ABSTRACTThis research is motivated by the students understanding on mathematics concept that still low and students not interest in learning mathematics. This research was aimed at revealing whether the use of bingo review strategies could give a better effect on the studentsâ understanding on mathematics concept than the conventional one in class VIII of MTsN Bariang Rao- Rao. This was an experimental research which used random research design toward the subject. The instrument used in this research is a test in studentsâ understanding on mathematics concept. The data Â was analyzed by using t-test assisted with software MINITAB. Based on the result of data analysis, it was revealed that the sample was distributed normally and had homogeny variant. Hypothesis test results obtained P - value = 0.000 was smaller than Î± = 0.05, Â indicating that the hypothesis was accepted. So, it was concluded that the application of bingo review strategies could improve the studentsâ understanding on mathematics concept, and better than the conventional one.